PEMBUATAN MESIN PENGUPAS DAN PEMERAS TEBU: PEMBUATAN MESIN PENGUPAS DAN PEMERAS TEBU - Veranika, Rita Maria; Madagaskar, Madagaskar; Aprilyanti, Selvia; Aprianti, Tine (Politeknik Negeri Sriwijaya, Indonesia, 2022)
Sugarcane is one of Indonesia's agricultural commodities which is quite large in production, sugarcane processing in Indonesia is usually used as sugar and flavoring, but sugar cane is also used by the community as a raw material for beverages, namely sugarcane ice. Sugarcane grinding machines or sugarcane squeezer machines are using for the process of separating sugarcane juice from sugarcane stem fiber, with the help of a sugarcane squeezer machine it will produce a lot of sugarcane juice, and only requires a short working time. The use of a sugar cane squeezer machine for producing sugar and making ice cane with a small-scale machine, so that it does not require space and a complicated process, this machine is very suitable for small and medium scale sugarcane processing industry. The purpose of this research is to design and manufacture a sugarcane squeezer machine using a combustion engine. The implementation method in the manufacture of this machine uses a propulsion system including combustion motors, pulleys, v-belts, gears, shafts, pegs, rollers and bearings. The results obtained from the design and manufacture of this sugarcane squeezer machine are that the energy and time that have been used are more efficient and the sugarcane processing is faster than manually. The design specifications of the tool are 0.5Hp engine capacity, 220 volt voltage and 2500 rpm rotation. Testing of the sugarcane juice machine is carried out to find out the results of the design can function according to the expected design